Hydrothermal treatment of lignocellulose waste for the production of polyhydroxyalkanoates copolymer with potential application in food packaging. (May 2022) - Tripathi, Abhishek Dutt; Mishra, Pradeep Kumar; Darani, Kianoush Khosravi; Agarwal, Aparna; Paul, Veena
Abstract: Background: Bio-plastics are eco-friendly biopolymer finding tremendous application in food and pharmaceutical industries. Biodegradable polymer-based plastic such as PHAs (plyhydroxyalkanoates) possesses similar physicochemical and mechanical properties as posed by conventional plastic. PHAs does not cause any type of hazardous pollution upon disposal. However, the high production cost of PHAs makes its wider acceptability unsuitable at commercial level. This can be minimized by screening potential PHAs producing strains, selecting inexpensive raw material, optimized cultivation condition and by adopting efficient recovery and purification strategies. Scope and approach: The PHA upstream processing is expensive and contributes approximately 40% of total production cost. This can be minimized to greater extent by using inexpensive raw materials such as agro-industrial waste and lignocellulose waste (LCW). In recent time, LCW has gained more attention in bioprocess-based production owing to its nutritional composition. LCW is rich in complex polysaccharides such as lignin, cellulose, hemicellulose which are not easily digested. Hydrothermal processing of lignocellulosic materials causes a variety of effects including extractive removal, hemicellulose hydrolysis and alteration of the properties of both cellulose and lignin. The extracted digested residues can be effectively utilized in PHAs and copolymer synthesis. Key findings and conclusion : This review focusses on various aspects of hydrothermal processing of lignocellulosic waste for efficient and economical PHAs production. These bio-plastics specifically microbial produced bio-polymers such as PHAs find application in food industries as packaging material owing to their desirable water barrier and gas permeability properties in addition to complete biodegradability upon disposal without green-house gas emission. The present review deals with the production, recovery, purification, characterization and applications of PHAs and its copolymers using LCW as potential substrate. This review will also focus on different strategies adopted for efficient PHA production using hydrothermal treated LCW, its biosynthetic mechanism, extraction, purification, characterization and also biodegradability testing at lab and pilot plant level. In addition to that, the authors will emphasize novel PHA copolymers nanocomposites synthesis strategies and their commercial applicability. Graphical abstract: Image 1 Highlights: The agro-waste rich in lignocellulose are potential substrate for PHA production. The hydrothermal pretreatment of lignocellulosic waste promotes the PHA production. Biodegradability of produced PHA expands its application value. ASTM standards and biodegradability of PHAs.